2021
DOI: 10.1021/acsami.1c05706
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of Microscopic Structure and Functionality during Crystallization of Amorphous Indium-Based Oxide Films

Abstract: Understanding the crystallization mechanism of amorphous metal-oxide thin films remains of importance to avoid the deterioration of multifunctional flexible electronics. We derived the crystallization mechanism of indium-based functional amorphous oxide films by using in situ X-ray diffraction (XRD) and transmission electron microscopy (TEM) measurements. Crystallization begins with surface nucleation, especially at low annealing temperatures, and proceeds simultaneous nucleation and growth in the bulk. Three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Thus, we find that the structural, dynamic, and electronic properties reach their corresponding crystalline or amorphous bulk values within about 2 Å, making our choice of a 20 Å model sufficient to describe the c/a interface. The sharp c/a interface obtained in our calculations is in accord with the high-resolution TEM imaging of nanocrystallites in amorphous indium oxide …”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, we find that the structural, dynamic, and electronic properties reach their corresponding crystalline or amorphous bulk values within about 2 Å, making our choice of a 20 Å model sufficient to describe the c/a interface. The sharp c/a interface obtained in our calculations is in accord with the high-resolution TEM imaging of nanocrystallites in amorphous indium oxide …”
Section: Resultssupporting
confidence: 88%
“…It must be stressed that the oxygen stoichiometry, cation composition, or density of amorphous indium oxide may influence the formation and concentration of stable In–OH, In–H–In, and O 2 defects and, hence, is likely to affect both the crystal grain size and the crystallization rate, explaining a wide variety of experimental observations reported in the literature. In addition, the film thickness and density and the oxygen environment during annealing are important control parameters of the crystallization process. , To address the effects of those parameters computationally, models of an amorphous oxide surface or a slab would be required in order to properly simulate surface defects, oxygen adsorption, diffusion, and defect passivation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Jia et al reported on the temporal evolution of microscopic structure and functionality during the crystallization of amorphous indium‐based oxides such as ITO and InGaO. [ 46 ] According to their work, nanocrystalline phases may be transformed out of the amorphous matrix of such AOSs, of which the process is facilitated by the support of oxygen vacancy migration, also known as structural relaxation. These potential instabilities of the amorphous phase and the associated change in the conduction path may be, at least in part, related to the demonstrated memristor performance issues regarding stability and endurance.…”
Section: Resultsmentioning
confidence: 99%